(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The present paper points out the variable forms that an image can assume,from the form of living divine being, as symbol of sovereignty, war trophiesand as object of sculptural art, depending on the changing context, setting,presentation and most significantly on the perceptions of a viewer. The paper shall deal with female forms ofidols particularly of Yakshi and would seek its transition from an independentpowerful deity whose worship was widely spread once, to its eventual absorptionand marginalization by the dominant religious traditions in ancient times andfinally its coexistence with the Brahmanic deities among the rural communitiesin present times. Furtherw, it will emphasize on the changing perceptionstowards "Once Goddess Yakshi" in contemporary period and how she isperceived, experienced and interpreted by various communities and by differentpeople.